Rereading Walter Pater - Shuter, William (Cambridge studies in nineteenth-century literature and culture., 1997)
Walter Pater is increasingly gaining recognition as a pivotal figure in nineteenth-century culture. His later work is often regarded as an effort to distance himself from his earlier, more controversial texts. In this 1997 book, William F. Shuter argues that Pater's writings demand a twofold reading. Shuter first offers an account of the texts in the order in which they were written, paying close attention to the changes in Pater's thought and interests over time; he then returns to the earlier texts, showing how the later work serves, paradoxically, as an introduction to the earlier. Drawing extensively on unpublished manuscript material, Shuter reveals that Pater himself authorised rereadings of his work in an effort to rewrite his own literary past and the past of his culture. This perspective on Pater's work uncovers patterns of continuity and anticipation that decisively alter our understanding of Pater and his writings.